(untitled) (Comprehensive Journal of Science, 2026)
This study aimed to determine the level of social responsibility and academic performance among faculty members at the Faculty of Education, Zuwara - University of Zawia, and to explore the nature of the correlational relationship and predictive power between them. To achieve this, the study adopted a descriptive-analytical correlational approach. It was applied to a random sample of (42) faculty members, representing approximately 41% of the original population of (101). A questionnaire was used as the primary data collection tool after verifying its validity and reliability. Field results revealed a "high" level of social responsibility practice, with an arithmetic mean of (4.192). Commitment to instilling national values, protecting social heritage, and community reform emerged at the forefront of academic concerns with a "very high" rating. Regarding the correlational aspect, the results of simple linear regression analysis proved the existence of a statistically significant positive relationship (0.023) between the two variables. This confirms that social responsibility acts as a "performance driver," contributing (12.3%) to explaining the variance in the level of academic performance. The study concluded that a university professor’s awareness of their role toward society instinctively drives them to improve their teaching, research, and supervisory practices. Accordingly, the study recommended the necessity of enhancing the culture of social responsibility and integrating its standards into annual performance evaluation forms for academics, while working to overcome organizational and administrative obstacles that may hinder the optimal activation of the university professor’s societal role.